AGGRESSIVE BEHAVIOUR AMONG ADOLESCENTS IN ARAB SCHOOLS A LITERATURE REVIEW (Journal of Academic Research, 2022)
Numerous studies have focused on the individual characteristics of aggressive behaviuor with the studies not making a careful examination of contextual factors that might influence the aggressive behaviour among adolescents in the Arab world. This paper is a literature reviewthat identifies the strengths and weaknesses of the previous studies;it aims at providing a strategy to reduce the level of aggressive behavior among adolescents in Arab schools. Furthermore, it gives full explanation of the issues and difficultiesthat provide meaningful information as guidance for researchers and counselors in this field.
Keywords: Aggressive; Behaviour; Adolescents